2017
DOI: 10.3390/ijms18030677
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci Conditioning the Main Biomass Yield Components and Resistance to Melampsora spp. in Salix viminalis × Salix schwerinii Hybrids

Abstract: The biomass of Salix viminalis is the most highly valued source of green energy, followed by S. schwerinii, S. dasyclados and other species. Significant variability in productivity and leaf rust resistance are noted both within and among willow species, which creates new opportunities for improving willow yield parameters through selection of desirable recombinants supported with molecular markers. The aim of this study was to identify quantitative trait loci (QTLs) linked with biomass yield-related traits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…With the aim of identifying markers for MAS, different QTL studies have been conducted in Populus and Salix species to understand the genetics of different disease resistance traits (Jorge et al, 2005; Rönnberg-Wästljung et al, 2008; Hanley et al, 2011; Samils et al, 2011), phenology and biomass related traits (Dillen et al, 2009; Rae et al, 2009; Wullschleger et al, 2011; Berlin et al, 2014, 2017; Ghelardini et al, 2014). More recently association mapping studies have been performed that identified putative causative genes for growth and phenology traits in Salix and in Populus species (Allwright and Taylors, 2016; Fahrenkrog et al, 2016; Hallingbäck et al, 2016; Carlson et al, 2019) and for traits related to chemical wood properties (Wegrzyn et al, 2010; Guerra et al, 2013; Porth et al, 2013; Muchero et al, 2015; Carlson et al, 2019), all that are of potential interest for breeding purposes.…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of identifying markers for MAS, different QTL studies have been conducted in Populus and Salix species to understand the genetics of different disease resistance traits (Jorge et al, 2005; Rönnberg-Wästljung et al, 2008; Hanley et al, 2011; Samils et al, 2011), phenology and biomass related traits (Dillen et al, 2009; Rae et al, 2009; Wullschleger et al, 2011; Berlin et al, 2014, 2017; Ghelardini et al, 2014). More recently association mapping studies have been performed that identified putative causative genes for growth and phenology traits in Salix and in Populus species (Allwright and Taylors, 2016; Fahrenkrog et al, 2016; Hallingbäck et al, 2016; Carlson et al, 2019) and for traits related to chemical wood properties (Wegrzyn et al, 2010; Guerra et al, 2013; Porth et al, 2013; Muchero et al, 2015; Carlson et al, 2019), all that are of potential interest for breeding purposes.…”
Section: Introductionmentioning
confidence: 99%
“…S. purpurea in vitro plantlets were obtained by bud culture of the PSP33 genotype selected from the Salix purpurea germplasm collection at the University Warmia Mazury in Olsztyn (Poland) (Sulima et al, 2017a(Sulima et al, , 2017b(Sulima et al, , 2017c. The conditions for in vitro tissue culture were previously optimized for S. purpurea genotypes (Gomes et al, 2019).…”
Section: Plant Materialsmentioning
confidence: 99%
“…In closely related pathosystems, including poplar rust caused by M. larici-populina or ax rust caused by M. lini, research has identi ed speci c quantitative and qualitative rust resistance using candidate gene analysis and QTL mapping approaches (16)(17)(18)(19)(20)(21). Most research in the Salix -Melampsora pathosystem has focused on S. viminalis and M. larici-epitea (22)(23)(24). While S. viminalis is well-adapted and popular in European bioenergy willow breeding programs, S. purpurea is most commonly used in the US.…”
Section: Introductionmentioning
confidence: 99%